Analysis of benzene as an indicator of air quality in fuel establishments - Dongo-Cateriano, César (2022)
The fuel trading activity carried out at taps and/or service stations generates a series of environmental impacts that alter the quality of the environmental components; In this sense, the Directorate of Environmental Affairs of Hydrocarbons of the Ministry of Energy and Mines and the Protocol of Environmental Quality of the Air of the Ministry of the Environment have determined that benzene is found in liquid fuels, and this would be an identified parameter to carry out. the follow-up of the environmental quality of the air through environmental monitoring, which is carried out in accordance with the provisions of the environmental management instruments approved by the Environmental Authority. The present article carried out an analysis according to the results of the benzene parameter obtained in the environmental monitoring carried out during the year 2018 in various Establishments that commercialize liquid fuels, with which it was analyzed that in the four evaluated quarters of 2018, benzene only exceeded the RCT for air at three points, which represented 2% of the analyzed data. It was concluded that benzene is not representative for monitoring air quality in establishments where fuel is sold.